Kajian Design Requirfaient Kapal Waterways Provinsi Dki - Hardjono, Soegeng (Warta Penelitian Perhubungan, 2010)
Design requirement is stmu:fard requirernent tluzt should be met and carried out before introducing akind of newly transportation mode. Sudi matter luzd e-uer been experienced recently bi; the PravinceGovernment of OKI as tnjing to introduce newly transportation rrwde so called waterways besidebus way as a part of macro transportation sd1eme (PTM). During initial. operation trials, the vesselsJuul faced many difficulties and obstacles because of her unsuitable design. In realih;, the existing rivervessels namely KM K.erapu III and KM K.ernpu IV m~re preuiously used for sen transportation. TI1e1;could not fulfill the conditim1 of existing rirer environment bemuse their design requirement Juul notbeen m1ailnble and azrried out yeL Draft of tllt'se uessels npproxinmtely 0.6 m Juul become obstacle tooperate in the existing river having depth of about 1 meter or even less. After conducting an analysison design requirement for required river transport, it is finally founded that the suitable river vesselwould have a twin-hull vessel as known as catamaran which has a displacement hull h;pe, made ofFRP, with main dimensions of 9.95m length, 3.20111 width, 1.20m depth, 25knots speed, 25 personscapacitt;, 145/rp, and slenderness ratio I.;b=9. Howerier, dredging effort should be recommended tomaintain river depth at least 1 m or e-uen more and 111ake sure that the proposed riessel may runsmoothly during her operation nnd free fro111 dependenci; from open-closed si;stem of water gate inmaintaining the water depth lend.Keywords: Watenuays, West Flood Canal, Catamaran vessel, Principal dimensions, PravinceGovernment of D KI